Phytosanitary practices adopted by small vegetable and fruit producers in the Sobradinho Area in Uberlandia Municipality, Minas Gerais (MG) State, Brazil (Research, Society and Development, 2024)
The production of vegetables and fruit is essential for small farmers in Minas Gerais. Many of these producers only use chemical products to control pests and diseases. However, inappropriate use, such as applying at the wrong time or in the wrong doses, can cause resistance in insects and fungi. This leads to the need to use larger quantities of products and the development of new products, which are more harmful to the environment and to beneficial insects. This investigation aims to understand the phytosanitary aspects and management practices of small-scale vegetable and fruit producers in the Sobradinho region of Uberlândia - MG. It also aims to provide information and guidance on different ways of controlling pests and diseases. A social survey (carried out with people) was carried out using questionnaires composed of open and structured questions, addressing the socio-educational profile of farmers, production practices and the species of vegetables and fruit grown. The data was collected through questionnaires sent electronically and through face-to-face visits. During the project, eight producers were interviewed, who expressed a great need for information on sustainable practices and effective alternatives for phytosanitary management.